A programmable magnetic digital microfluidic platform integrated with electrochemical detection system - Zhao, Yong; Jiang, Shuyue; Cai, Gaozhe; Wang, Lihua; Zhao, Jianlong; Feng, Shilun (Microsystems & nanoengineering, 2025)
Digital microfluidic (DMF) technology is widely used in bioanalysis and chemical reactions due to its accuracy and flexibility in manipulating droplets. However, most DMF systems usually rely on complex electrode fabrication and high driving voltages. Sensor integration in DMF systems is also quite rare. In this study, a programmable magnetic digital microfluidic (PMDMF) platform integrated with electrochemical detection system was proposed. It enables non-contact, flexible droplet manipulation without complex processes and high voltages, meeting the requirements of automated electrochemical detection. The platform includes a magnetic control system, a microfluidic chip, and an electrochemical detection system. The magnetic control system consists of a microcoil array circuit board, a N52 permanent magnet, and an Arduino control module. N52 magnets generate localized magnetic fields to drive droplet movement, while the Arduino module enables programmable control for precise manipulation. The maximum average velocity of the droplet is about 3.9 cm/s. The microfluidic chip was fabricated using 3D printing and the superhydrophobic surface of chip was fabricated by spray coating. The electrochemical detection system consists of the MoS 2 @CeO 2 /PVA working electrode, Ag/AgCl reference electrode, and carbon counter electrode. To evaluate the practical value of the integrated platform, glucose in sweat was automatically and accurately detected. The proposed platform has a wide linear detection range (0.01–0.25 mM), a lower LOD (6.5 μM), a superior sensitivity (7833.54 μA·mM −1 ·cm −2 ), and excellent recovery rate (88.1–113.5%). It has an extensive potential for future application in the fields of medical diagnostics and point-of-care testing.